2017
DOI: 10.1038/s41437-017-0018-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of historical land use and modern agricultural expansion on the spatial and ecological divergence of sugarcane borer, Diatraea saccharalis (Lepidoptera: Crambidae) in Brazil

Abstract: Human-mediated changes in landscapes can facilitate niche expansion and accelerate the adaptation of insect species. The interaction between the evolutionary history of the sugarcane borer, Diatraea saccharalis Fabricius, and historical and modern agricultural activity in Brazil shaped its spatial genetic structure, facilitating ecological divergence and incipient host shifting. Based on microsatellite data, STRUCTURE analyses identified two (K = 2) and three (K = 3) significant genetic clusters that correspon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 80 publications
4
19
0
1
Order By: Relevance
“…Incipient signals of this divergence among SCB populations collected on various host plants (sugarcane and maize) were already observed by Pavinato et al. (), highlighting the importance to know the impact of this divergence on the gene flow among populations of SCB to develop sustainable pest control methods.…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…Incipient signals of this divergence among SCB populations collected on various host plants (sugarcane and maize) were already observed by Pavinato et al. (), highlighting the importance to know the impact of this divergence on the gene flow among populations of SCB to develop sustainable pest control methods.…”
Section: Introductionmentioning
confidence: 77%
“…(, ), and Pavinato et al. (). In accordance with these studies, our results demonstrated pre‐ and post‐zygotic incompatibility in combinations of SCB populations in association with different host plants and differences in geographical distance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations